Boolean Calcium Signalling Model Predicts Calcium Role in Acceleration and Stability of Abscisic Acid-Mediated Stomatal Closure. Issue 1 (December 2018) - Waidyarathne, Pramuditha; Samarasinghe, Sandhya
Abstract Inconsistent hypotheses have proposed Ca2+ as either being essential or irrelevant and redundant in ABA induced stomatal closure. This study integrates all available information from literature to define ABA signalling pathway and presents it in a systems view for clearer understanding of the role of Ca2+ in stomatal closure. Importantly, it incorporates into an Asynchronous Boolean model time delays sourced from an extensive literature search. The model predicted the timing of ABA events and mutant behaviour close to biology. It revealed biologically reported timing for Ca2+ activation and Ca2+ dynamics consistent with biology. It also predicts that Ca2+ elevation is not essential in stomatal closure but it can accelerate closure, consistent with previous findings, but our model further explains that acting as a mediator, Ca2+ accelerates stomatal closure by enhancing plasma membrane slowly activating anion channel SLAC1 and actin rearrangement. It shows statistical significance of Ca2+ induced acceleration of closure and that of Ca2+ induced acceleration of SLAC1 activation. Further, the model demonstrates that Ca2+ enhances resilience of closure to perturbation of important elements; especially, ROS pathway, as did previous ABA model, and even to the ABA signal disruption. It goes further to elucidate the mechanisms by which Ca2+ engenders stomatal closure in these perturbations.